TINJAUAN KOREOGRAFI TARI SELENDANG DULANG DI SANGGAR ANGGAR NAN TUJUAH KECAMATAN KOTO XI TARUSAN PESISIR SELATAN - Rahayu, Ella Saimedita; Nerosti, Nerosti (SENDRATASIK UNP, 2019)
AbstractÂ This study aims to analyze the Selendang Dulang Dance Choreography in Sanggar Anggar Nan Tujuah, Koto XI Tarusan District, Pesisir Selatan Regency. This type of studywas qualitative with using analytical descriptive methods. The main instrument was the researcher and is was assisted by using supporting instruments such as stationery and camera. The data used in this study wasprimary and secondary data. Techniques ofdata collection were carried out by taking literature study, observation, interview and documentation. Techniques of data analysis were done by collecting, describing and making data conclusions. The result shows that the dance arrangement performed by choreographer Ramadhani is very clear both in terms of motion, floor design, top design, group composition, dancers, music, property and costume. The aspect of space with a large volume with the name of the motion are Manaiakan Padi Kaunggua, Bajalan di Ateh Pamatang, Mambantiang Kain. On a small volume there is the motion names likeMangirai Kain, Mangayak Padi, Buai Buai, Anak Main, Manokang Padi. Arah is facing forward on the motion ofSerak Baniah, Buai Buai, anak main, Manjulang padi, Manokang Padi.Rotating motion there is the name ofAlang Babega, Puta Alang Babega. Themiddle level is contained on the motion AlangBabega, Dayuang SuokKida, Puta AlangBabega, Maragang kain, Rantak Cupu Manampi padi, Lenggang Karaia, MangipehPadi, Scatter Baniah.Thehigh level is found in the movements of Alang Babega, Manaiakan Padi, Kaunggak, Buai Buai Manjulang Padi.Meanwhile, the low level of Dayuang Suok Kida, Mangirai Kain, Mangayak Padi. In aspects of time there are tempo and rhythm that are found in the movement ofDayuang Suok Kida, Puta Alang Babega, Maragang Kain, Mambantiang Kain.Theslow tempo is found in the movements of Alang Babega and Sembah Penutup. Thehigh rhythm, there are names of Rantak Cupu, Manampi Padi,Lenggang Karaia, Manaiakan Kaunggua padi, Baniah Serak, Buai Buai, Anak Main, Manjulang Padi, Manokang Padi.Â The Selendang Dulang dance floor design consists of curved straight lines, straight lines that form triangles, zig zags, rhombus, and diagonal lines. The curved line floor design forms a full circle and half circle. Overall choreography, especially in energetic dance movements with maximum use of space and energy, through delayed design with shawl and dulang property, is very harmonious accompanied by the gandang tambua and tasa musical instruments that play an important role in the Selendang Dulang Dance choreography.Keywords: Choreography, Selendang Dulang Dance, Sanggar Anggar Nan Tujuah, Koto XI Tarusan District